2003
DOI: 10.1159/000074152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inguinal Dissection on Prognosis of Early-Stage Squamous Cell Carcinoma of the Vulva – a Retrospective Analysis

Abstract: Background: Inclusion of inguinal lymphadenectomy in the surgical procedure is a potential prognostic factor for squamous cell vulvar carcinoma. Patients and Methods: A total of 33 women with early-stage squamous cell vulvar carcinoma were analyzed retrospectively. Before the establishment of FIGO criteria in 1983, 17 patients with stage I and 2 patients with stage II were evaluated clinically without inguinal lymphadenectomy. All patients underwent post-operative radiotherapy with a median dose of 45 Gy to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(21 reference statements)
0
2
0
1
Order By: Relevance
“…Differentiation of the tumor (low [grade 1] vs poor [grade 2-3]) was found as an important prognostic factor in multivariate analyses (for MVA: HR 1-3.11, 95% CI 1.6-4.62, p = 0.0057). Other retrospective data including 33 patients with vulvar cancer found that differentiation grade was an independent predictor for decreased survival with a relative risk up to 2.6 (95% CI 1.3, 5.6) (13).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of the tumor (low [grade 1] vs poor [grade 2-3]) was found as an important prognostic factor in multivariate analyses (for MVA: HR 1-3.11, 95% CI 1.6-4.62, p = 0.0057). Other retrospective data including 33 patients with vulvar cancer found that differentiation grade was an independent predictor for decreased survival with a relative risk up to 2.6 (95% CI 1.3, 5.6) (13).…”
Section: Discussionmentioning
confidence: 99%
“…Early stage vulvar squamous cell carcinoma confirmed no inguinal lymph node metastasis pathologically, but a 11% to 43% probability of lymph node micrometastasis exists [9]; Gonzalez and Bosquet reported a retrospective study of 320 patients with vulvar cancer who had undergone surgery; of all 214 cases without suspicious inguinal lymph node metastasis, 48 patients (22.4%) exhibited occult lymph node metastases [10]. In these cases it is necessary to resect the bilateral inguinal lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…bestand nicht [1]. Allerdings stellt die sauber ausgeführte inguinale Lymphknotendissektion einen positiven Prognosefaktor bei der chirurgischen Therapie des Vulvakarzinoms dar [17]. Analog dazu ist ein inguinales Lymphknotenrezidiv oder die bilaterale Metastasierung jeweils mit einer schlechteren Prognose behaftet [11].…”
Section: Vulvakarzinomunclassified